Development of an Efficient G‐Quadruplex‐Stabilised Thrombin‐Binding Aptamer Containing a Three‐Carbon Spacer Molecule. (15th March 2017) - Aaldering, Lukas J.; Poongavanam, Vasanthanathan; Langkjær, Niels; Murugan, N. Arul; Jørgensen, Per Trolle; Wengel, Jesper; Veedu, Rakesh N.
Abstract: The thrombin‐binding aptamer (TBA), which shows anticoagulant properties, is one of the most studied G‐quadruplex‐forming aptamers. In this study, we investigated the impact of different chemical modifications such as a three‐carbon spacer (spacer‐C3 ), unlocked nucleic acid (UNA) and 3′‐amino‐modified UNA (amino‐UNA) on the structural dynamics and stability of TBA. All three modifications were incorporated at three different loop positions (T3, T7, T12) of the TBA G‐quadruplex structure to result in a series of TBA variants and their stability was studied by thermal denaturation; folding was studied by circular dichroism spectroscopy and thrombin clotting time. The results showed that spacer‐C3 introduction at the T7 loop position (TBA‐SP7) significantly improved stability and thrombin clotting time while maintaining a similar binding affinity as TBA to thrombin. Detailed molecular modelling experiments provided novel insights into the experimental observations, further supporting the efficacy of TBA‐SP7. The results of this study could provide valuable information for future designs of TBA analogues with superior thrombin inhibition properties. Abstract : Give me some space ! We investigated the impact of three different chemical modifications: a three‐carbon spacer (spacer‐C3 ), unlocked nucleic acid (UNA) and 3′‐amino‐modified UNA on the structural dynamics and stability of the thrombin‐binding aptamer. The results showed that spacer‐C3 introduction at the T7 loop position significantly improved stability and thrombin clotting time.